Jørgen Pedersen on Fiscal policy - A note - Finn Olesen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2001)
With The General Theory Keynes initiated a true revolution in the field of economics putting forward a new way of reasoning which gave way to modern views on economic policy. However, he was not the only one who thought along these lines in the 1930s. Jørgen Pedersen, who was to become the founding father of the Keynesian tradition in Denmark, also made some early contributions. In the 1933-article Economic Stabilization he presented a clear macroeconomic way of reasoning. Later on in the 1937-article Some Problems of Public Finance he discussed some important problems concerning how to use fiscal policy properly. In both articles Pedersen took a remarkable clear Keynesian position.
Keywords: 330; Finanzpolitik